A Discriminant Analysis of Factors Decision to Study The Undergraduate Program in Saengtham College. - Srithai, Kanvasu; Langka, Wilailak (Saengtham College Journal, 2023)
The purposes of this research are as follows: 1) to compare the factors affecting students’ decision to choose to pursue further study, and 2) to study discrete factors affecting students’ decision to choose to pursue further study. The samples consisted of 182 undergraduate students studying in the academic year 2022, selected by purposive sampling. The instrument used for data collection was 1 copy of a questionnaire on discriminant factors affecting students’ decision to study at the undergraduate level of Saengtham College, a 5-level estimation scale consisting of 55 items which were divided into personal factors, marketing mix, and psychological factors. The discriminant power (r) ranged from 0.22 - 0.94 and the reliability was 0.96. The data were analyzed using a ready-made processing program to find percentage, mean, standard deviation, and discriminant analysis. The study found that: A comparison of the differences in factors among students who made a decision to choose to study differently found that the factors of family income, product, price, place, promotion, people, process, physical evidence, future expectations in religious work, motivation for religious work and attitudes towards religious leaders were different as a statistically significant a level of .01 which indicated that the factors used in this study affected students’ decision to choose to continue their studies. This is in line with the results of the discriminant factor analysis that affects the student’s decision to choose to study further. There were 11 factors that were recruited into the discriminant equation, arranged in descending order of the standard coefficients, regardless of the sign, namely physical evidence, future expectations of religious work, product, family income, place, motivation for religious work, process, attitudes towards religious leaders, promotion, price, and people. The classification equation was able to predict the membership of different groups of students who decided to study in different groups correctly at 70.80 percent, with the classification equation. (Discriminant Function) as follows Y = .727(Physical) - .525(Expectation) + .510(Product) + .408(family income) + .369(Place) + .343(Motivation) - .335(Process) - .148(Attitude) + .077(Promotion) - .076(Price) + .056(People)